2020
DOI: 10.1021/acs.orglett.0c03126
|View full text |Cite
|
Sign up to set email alerts
|

Rhodium(III)-Catalyzed Alkenyl C–H Functionalization to Dienes and Allenes

Abstract: An oxyacetamide-directed Rh­(III)-catalyzed Z-type alkenyl C–H functionalization through a rare exo-rhodacyle intermediate is described, forming multisubstituted dienes and allenes. A variety of alkenes and propargylic carbonate coupling partners are suitable for this transformation with high regio- and stereoselectivity. The synthetic utility is demonstrated by the selective late-stage modification of the Z-type natural products as well as the synthesis of the unnatural β-amino acid.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 106 publications
0
9
0
1
Order By: Relevance
“…Lu and Zhao et al reported an oxyacetamide-directed Z-type alkenyl C−H functionalization enabled by a Cp*Rh(III) catalyst through a rare exo-rhodacyle process (Scheme 74). 162 Multisubstituted alkenes and allenes were synthesized in modest to excellent yields. With the judicious choice of solvents and base, both alkenes and propargylic carbonates coupling partners reacted well to furnish the corresponding products with high regio-and stereoselectivity.…”
Section: Alkenyl C−h Bond Functionalization Of Aliphatic Alkenes Cont...mentioning
confidence: 99%
“…Lu and Zhao et al reported an oxyacetamide-directed Z-type alkenyl C−H functionalization enabled by a Cp*Rh(III) catalyst through a rare exo-rhodacyle process (Scheme 74). 162 Multisubstituted alkenes and allenes were synthesized in modest to excellent yields. With the judicious choice of solvents and base, both alkenes and propargylic carbonates coupling partners reacted well to furnish the corresponding products with high regio-and stereoselectivity.…”
Section: Alkenyl C−h Bond Functionalization Of Aliphatic Alkenes Cont...mentioning
confidence: 99%
“…In absence of Cu(OAc In the year 2020, Zhao and co-workers reported Rh(III)-catalyzed cross dehydrogenative coupling of alkenyl oxyamides 113 with alkenes 114, in which oxyacetamide was utilized as the directing group (Scheme 48). 83 [RhCp*Cl 2 ] 2 was used as the optimal catalyst with silver carbonate as the oxidant at room temperature. Acrylates, acrolein, ethyl vinyl ketone, styrenes, and heterocyclic alkenyl coupling partners were found to be suitable substrates in this transformation and generated desired products 115 in reasonable yields with high regio-and Scheme 47 Pd(II)-catalyzed C-H alkenylation of alkenyl alcohols 106, carbamates 107, and amides 108.…”
Section: Organic and Biomolecular Chemistry Reviewmentioning
confidence: 99%
“…In 2020, Zhao, Lu and co-workers reported a Rh( iii )-catalysed diene synthesis directed by the oxyacetamide group (–ONHAc) through the formation of a five-membered exo -rhodacycle (Scheme 4). 16 Steroid-derived oxyacetamide was successfully synthesized in 83% yield from 1-testosterone which is an active molecule for treating male endogenous androgen deficiency.…”
Section: Cross-dehydrogenative Coupling Of Alkenesmentioning
confidence: 99%